Structurally Stable Manganese Alkoxide Films Grown by Hybrid Molecular Layer Deposition for Electrochemical Applications. (15th August 2019) - Bergsman, David S.; Baker, Jon G.; Closser, Richard G.; MacIsaac, Callisto; Lillethorup, Mie; Strickler, Alaina L.; Azarnouche, Laurent; Godet, Ludovic; Bent, Stacey F.
Abstract: Hybrid molecular layer deposition (MLD) has significant potential for the creation of ultrathin electrochemically active materials, due to its ability to combine organic and inorganic species to modulate film properties. However, only a limited number of hybrid MLD processes are demonstrated with electrochemically relevant elements, such as manganese. Here, a "manganicone" manganese hybrid MLD chemistry is developed using the precursors bis(ethylcyclopentadienyl)manganese and ethylene glycol. The resulting manganese alkoxide coordination networks are shown to have many interesting properties, including the ability to seamlessly fill high aspect ratio vias and the chemical conversion into manganese carboxylate in air over several hours at room temperature. Linear, self‐saturating growth is reported. Importantly, hybrid manganicone films annealed to 480 °C in air demonstrate a greater stability to restructuring during electrochemical testing than their inorganic counterparts grown by atomic layer deposition, without reducing the activity of the reactive sites on the manganese surface. Thus, hybrid manganese films grown by MLD have significant promise for use as catalysts for the oxygen evolution reaction and as electrodes in thin film batteries. Abstract : A structurally stable manganese alkoxide‐based electrochemically active film is achieved using the layer‐by‐layer molecular layer deposition process. The alternating vapor‐phase exposures to a Mn‐precursor and ethylene glycol produces a manganese alkoxide thin film that reacts with air to form manganese carboxylate. Pyrolysis of the carboxylate produces films that exhibit greater resistance to restructuring during electrochemical cycling than manganese oxide.